Comparison Based Analysis of Advanced Tree Structures - *, Monika (IJRDO -Journal of Computer Science Engineering, 2015)
In this paper, the comparison is done among the most commonly used tree data structures i.e. B-trees and binary trees. This comparison is made among all the variants of these trees on the basis of various operations done over them like creation, insertion, deletion, and searching. The steps needed for these operations are counted and compared. This study can help us to find out easily that which tree data structure can be used in an application to make it efficient.